2011
DOI: 10.1192/bjp.bp.110.085472
|View full text |Cite
|
Sign up to set email alerts
|

Persistent distress after psychological exposure to the Nagasaki atomic bomb explosion

Abstract: Having been in the vicinity of the atomic bomb explosion without radiological exposure continued to be associated with poorer mental health more than half a century after the event. Fear on learning about the potential radiological hazard and lack of knowledge about radiological risk are responsible for this association.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 14 publications
1
21
0
3
Order By: Relevance
“…In a review of the Chernobyl Forum in 2006, the WHO concluded that mental health disturbances were the most serious public health problem [18]. A previous study suggested that psychological exposure to the Nagasaki atomic bomb explosion, without substantial health harming radiological exposure, generated prolonged distress even after half a century, and that poor information provision contributed to this distress [19]. Our investigation concurs, as we found that for residents in areas of radioactive contamination, their perceived threat to health had a negative impact on their mental wellbeing, even though radioactivity rarely reached health-threatening levels.…”
Section: Discussionmentioning
confidence: 99%
“…In a review of the Chernobyl Forum in 2006, the WHO concluded that mental health disturbances were the most serious public health problem [18]. A previous study suggested that psychological exposure to the Nagasaki atomic bomb explosion, without substantial health harming radiological exposure, generated prolonged distress even after half a century, and that poor information provision contributed to this distress [19]. Our investigation concurs, as we found that for residents in areas of radioactive contamination, their perceived threat to health had a negative impact on their mental wellbeing, even though radioactivity rarely reached health-threatening levels.…”
Section: Discussionmentioning
confidence: 99%
“…Given the long-term psychological impact among atomic-bomb survivors (Lifton 1967; Ohta et al 2000; Honda et al 2002; Yamada and Izumi 2002; Kim et al 2011), along with anecdotal news reports and studies of volunteer populations after Fukushima, there is reason to believe that the long-term psychological and subjective health aftermath for mothers of young children will follow a similar pattern. In Ukraine, doctors often indiscriminately attributed the health concerns reported by mothers to radiation exposure from Chernobyl.…”
Section: Mothers Of Young Childrenmentioning
confidence: 99%
“…Ultimately, nonpsychiatrist physicians will also need to learn to recognize the signs and symptoms of mental health problems, including psychosomatic manifestations, and will need to know how to differentiate between genuine radiation-health effects and psychologically-driven or mediated concerns. It is very likely that for individuals directly impacted by Fukushima, as occurred among physically healthy survivors decades after the atomic-bomb explosion in Nagasaki (Kim et al 2011), the psychological distress occurring in the immediate aftermath of Fukushima will become chronic. Thus, long-term management will be required by both mental health professionals and nonmental health medical providers.…”
Section: Comment and Conclusionmentioning
confidence: 99%
“…A recent study (Kim et al 2011) shows that psychological exposure to Nagasaki atomic bomb explosion, without substantial health harming radiological exposure, generated prolonged distress after half a century and the poor information provision was correlated. A study after Chernobyl has shown that diagnosis of depression and PTSD increased among clean-up workers 18 years after the accident (Loganovsky et al 2008).…”
Section: Fukushima Nuclear Power Plant Accidentmentioning
confidence: 99%